+0

# CIRCLE

0
61
2
+148

Three circles of radius 1 are externally tangent to each other and internally tangent to a larger circle. What is the radius of the large circle? Express your answer as a common fraction in simplest radical form.

AdminMod2  Sep 3, 2017
Sort:

#1
+76198
+1

May be faster ways to do this, but look at the following:

Let the centers of two of the circles lie at (1,0)  and (-1,0)

So....to find the center of the third circle let it be located at  (0,y)

And by the Pythagorean Theorem we have

y = sqrt [ GD^2 - HD^2 ]

y= sqrt [ 2^2 - 1^2]  =  sqrt (3)

So the center of the top circle =  ( 0, sqrt (3) )  call this point  G

Let point E be the center of the circle.....and it will be located at (0, c )

Now let B be  the point tangent to the top circle and the leftmost circle

And its coordinates will be  the midpoint of  CG =   [ -1/2 , sqrt (3)/2 )

Let A be the intersection of the apex of the top circle and  the y axis.......and its coordinates  are

(0, GA + GH )  =  ( 0, 1 + sqrt (3) )

And....by similar triangles

(BF) / FD  = HE /HD

(sqrt [(3)/2] )   / (3/ 2)  =  HE / 1    →   HE  =  sqrt (3)/3

So....the radius of the large circle  = [AH - HE]  =  EA =

[1 +  sqrt (3)] -   [sqrt (3)/3]  =

1 + (2/3) sqrt (3)

CPhill  Sep 3, 2017
edited by CPhill  Sep 3, 2017
edited by CPhill  Sep 3, 2017
#2
+18566
+1

Three circles of radius 1 are externally tangent to each other and internally tangent to a larger circle.
What is the radius of the large circle?
Express your answer as a common fraction in simplest radical form.

Let Radius of the larger circle = R.
Let Radius of the three circles = r = 1.

Let Area of the triangle ABC = $$A_{ABC}$$
Let Area of the triangle AOB = $$A_{AOB}$$

Let AC = CB = BA = 2r
Let AO = OB = R-r

$$\mathbf{A_{ABC} = \ ?}$$

$$\begin{array}{|lrcll|} \hline (\text{Heron}) & s &=& \frac{2r+2r+2r}{2} \\ & &=& 3r \\ & A_{ABC}^2 &=& s(s-2r)(s-2r)(s-2r) \\ & A_{ABC}^2 &=& s(s-2r)^3 \quad & | \quad s = 3r \\ & A_{ABC}^2 &=& 3r(3r -2r)^3 \\ & A_{ABC}^2 &=& 3rr^3 \\ & A_{ABC}^2 &=& 3r^4 \\ & A_{ABC} &=& r^2 \sqrt{3} \\ \hline \end{array}$$

$$\mathbf{A_{AOB} = \ ?}$$

$$\begin{array}{|lrcll|} \hline & A_{AOB} &=& \frac{A_{ABC}}{3} \\ (1) & A_{AOB} &=& \frac{r^2 \sqrt{3}}{3} \\ \hline \end{array}$$

$$\mathbf{(\text{Heron})\ A_{AOB} = \ ?}$$

$$\begin{array}{|rcll|} \hline (\text{Heron}) & s &=& \frac{2r+(R-r)+(R-r)}{2} \\ & s &=& \frac{2R}{2} \\ & s &=& R \\ & A_{AOB}^2 &=& s(s-2r)[s-(R-r)][s-(R-r)] \quad & | \quad s = R \\ & A_{AOB}^2 &=& R(R-2r)[R-R+r)][R-R+r] \\ & A_{AOB}^2 &=& R(R-2r)r^2 \\ (2) & A_{AOB} &=&r\sqrt{R(R-2r)} \\ \hline \end{array}$$

(1) = (2)

$$\begin{array}{|rcll|} \hline \frac{r^2 \sqrt{3}}{3} &=& r\sqrt{R(R-2r)} \\ \frac{r \sqrt{3}}{3} &=& \sqrt{R(R-2r)} \quad & | \quad \text{square both sides}\\ \frac{r^2}{3} &=& R(R-2r) \\ R^2-2rR -\frac{r^2}{3} &=& 0 \quad & | \quad \cdot 3 \\ 3R^2-6rR - r^2 &=& 0 \\ \\ R &=& \frac{6r \pm \sqrt{36r^2-4\cdot 3\cdot (-r^2) } }{2\cdot 3} \\ R &=& \frac{6r \pm \sqrt{36r^2+12r^2 } }{6} \\ R &=& \frac{6r \pm \sqrt{48r^2 } }{6} \\ R &=& \frac{6r \pm 4r\sqrt{3} }{6} \\ R &=& r \pm \frac23 r \sqrt{3} \quad & | \quad R \gt 0 \\ R &=& r + \frac23 r \sqrt{3} \quad & | \quad r = 1 \\ \mathbf{R} & \mathbf{=} & \mathbf{1 + \frac23 \sqrt{3}} \\ \hline \end{array}$$

heureka  Sep 4, 2017

### 26 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details